Squeal occurrence related to the tracking of the bearing surfaces on a pin-on-disc system. (15th February 2022) - Lai, Van-Vuong; Paszkiewicz, Igor; Brunel, Jean-François; Dufrénoy, Philippe
Abstract: Brake squeal is an important issue in the automotive and railway industry with high frequencies and acoustic pressure (above 1 kHz and 80 dB). For the comfort of passengers, the generation mechanism of this noise needs to be investigated to propose mitigation solutions. Recent works show that the state of the rubbing surface has a strong influence on the occurrences. In this paper, we propose to consider the effect of contact localization on the occurrence of squeal through experiments on a pin-on-disc system close to the braking application. An in-operando and in-situ monitoring of the contact surface during tests is carried out with thermal tracking of the friction body through thermocouples inserted in the pin near the rubbing surface. Based on the thermal measurements, an inverse method is used to identify the heat dissipation zone. Assuming that this zone is equivalent to the macroscopic load-bearing area, a stability analysis is performed to determine the unstable frequencies from contact area. Correlations between numerical results with experiments show that the change of squeal frequencies agrees with the evolution of the contact localization at a macroscopic scale. This localization can then be considered as one of the key parameters linking the surface state and the occurrence of squeal. Highlights: Investigate rubbing contact area variations during friction tests by monitoring the contact surface with thermal tracking of the friction body through thermocouples. An inverse method is developed for the identification of macroscopic load-bearing zone from measured temperatures. Complex modal analysis of the system is performed with the identified contact zone to investigate the correlation between contact localization and the occurrence of squeal. The change of squeal frequencies agrees with the evolution of the contact localization at a macroscopic scale. The evolution of the contact localization at a macroscopic scale can be considered as one of the keys linking the surface state and the occurrence of squeal.